2004
DOI: 10.2486/indhealth.42.79
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Waterproof Covering on Finger Skin Temperature and Hand Pain during Immersion Test for Diagnosing Hand-arm Vibration Syndrome

Abstract: The purpose of this study was to examine the influence of waterproof covering on finger skin temperature (FST) and hand pain during immersion test for diagnosing hand-arm vibration syndrome complying with the proposal of the International Organization for Standardization (ISO/ CD14835-1, 2001) for measurement procedure. Six healthy male subjects took part in the immersion tests and immersed their both hands into water at 12°C for 5 min, repeatedly with two types of waterproof covering (polyethylene and natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…This trend may have been caused by the retarded heat exchange due to the wearing of gloves. Wearing gloves could prolong the ET to reach a given FST (Clark & Cohen, 1960) or delay the reduction in FST at a given endurance time (Suizu et al, 2004;Suizu & Harada, 2005). A lower FST associated with wearing gloves first numbs the hands, and gradually impairs the hand function and performance (such as dexterity, sensitivity, and strength generation), eventually leading to frostbite and damage to the hands.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This trend may have been caused by the retarded heat exchange due to the wearing of gloves. Wearing gloves could prolong the ET to reach a given FST (Clark & Cohen, 1960) or delay the reduction in FST at a given endurance time (Suizu et al, 2004;Suizu & Harada, 2005). A lower FST associated with wearing gloves first numbs the hands, and gradually impairs the hand function and performance (such as dexterity, sensitivity, and strength generation), eventually leading to frostbite and damage to the hands.…”
Section: Discussionmentioning
confidence: 99%
“…At first, rapid heat dissipation occurs between two objects in contact due to a great difference in temperatures, accompanied by a rapid decrease in FST, a noticeable sensation of cold, and associated induced pain. Wearing gloves could delay the reduction in FST and reduce the perception of pain (Suizu et al, 2004;Suizu & Harada, 2005), and it is supposed that wearing gloves could also extend ET. Consequently, it is worthwhile and interesting to identify the FST at the point of pain tolerance during cold immersion, for FST has been reported as a crucial factor affecting hand dexterity (Schiefer et al, 1984;Enander, 1984;Enander & Hygge, 1990;Brajkovic & Ducharme, 2003, Chen et al, 2010.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, gloves can insulate the hands against cold. For example, in a dialogue test of 12°C-water and 5-minute immersion to assess the hand-arm vibration syndrome (ISO/CD 14835-1, 2001), researchers have revealed that wearing gloves can not only reduce pain but also delay a decrease in finger skin temperature (FST) (Suizu et al, 2004;Suizu & Harada, 2005). In addition, Nag and Nag (2007), who evaluated the hazards and health complaints associated with fish processing activities in India, indicated that, during a 2-hour period of work, wearing latex gloves could improve the FST and HST, raise morale in female workers, and alleviate cold-induced symptoms.…”
Section: Referencesmentioning
confidence: 99%